Trust and Business Risk in a Research Institute's Operations - Domańska-Szaruga , Beata; Simiński , Przemysław (Management and Administration Journal, 2017)
he objective of the study is to put forward proposals for limiting the negative effects of business risk by establishing relations with contracting parties not only on the basis of formalized contracts delineating the terms and conditions of cooperation but also, and most importantly, on trust development. The recommendations are preceded by a synthetic presentation of the issue of trust in relations with contracting parties and an outline of a selection of elements of the process of risk identification and analysis in the research institute' s business operations